Specific performance diagnostic in laboratory and field of BMX-Racing - Meurer, R.; Schmidt, A.; Meyer, H.; Heine, O.; Nüsser, S.; Lötzerich, H. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
BMX Racing is an Olympic discipline and the BMX Sport is experiencing more attention. There is not much detailed information available about the sport specific requirements and the common performance tests are mostly transferred from road and track cycling. Method: Six high level BMX riders (mean ± SD: 16,2 yrs ± 1,2, 65,2 kg ± 5,1, 178 cm ± 0,01cm) performed a performance test in the laboratory with the individual BMX bike position (standing up). Therefore the bicycle ergometer was adjusted to transfer the individual bike setup on to the ergometer. First step was a standardised warm up, with a stepwise increasement of the resistance (watt), for 15 min. The test was performed until 200 watt was reached, mean lactate levels after the warm up were 1,92 mmol/l ± 0,25. Step two was a BMX start simulation, where the riders had to sprint for 5 sec., set up and resistance of the ergometer were similar to the start on a BMX bike. Peak Power Start (PPS) was 1311 w ± 154.17. Third step of the test protocol was a 15 sec. sprint test which is similar to the active exercise time on a BMX track. The test was accomplished in a isokinetic mode with a limit of rpm to determine Peak Power (PP). After the test, lactic acid was measured, regularly over 10 min to determine peak lactic values (PL). PP was 1283,75 w ± 135,44. PL was 7,43 mmol/l ± 1,59. To compare our data`s from the laboratory we measured PP and PL on a BMX track with portable power meter system. After one lap under race conditions PP was 990 w ± 178,9. Mean power over the first 5 sec at the start (MPS) was 427,90 w ± 132,65. PL was 5,81 mmol/l ± 1,12. Results: The results of the BMX performance test show very assimilable results to the data we measured on the BMX track with mobile powermeter systems. PP, LP in the laboratory was for all riders higher then on the track. The order of the measured values in the comparison of laboratory to track was significant. The order of PPS, MPS, PP, PL were identical. The rider with the highest values in the laboratory also had the highest values on the track, same structure for all riders. Discussion: The purpose of this project was to develop a test protocol for a BMX specific performance diagnostic in the laboratory.In our BMX performance test protocol we are able to investigate the rider`s individual performance and requirements of BMX racing performance under standardised conditions in the laboratory. The individual structure of the riders peak power, start power and lactic acid production are reflecting very closely the individual physiological performance on the track.